Alpine plant communities in the Picos de Europa calcareous massif (Northern Spain) - Jiménez-Alfaro, Borja; Alonso Felpete, José Ignacio; Bueno Sánchez, Álvaro; Fernández Prieto, José Antonio (Lazaroa, 2014)
Mountains of Southern Europe are important refuges for cold-adapted plants, and the characterization of vegetation diversity in these areas is a relevant topic for biodiversity conservation. Here we report a comprehensive classification of plant communities in the highest altitudinal belt of the Picos de Europa, a biodiversity hotspot of Northern Iberian Peninsula. We compiled vegetation plot data sampled in the three calcareous massifs from 1800 to 2600 m.a.s.l., and analysed species composition by using cluster analyses and Nonmetric Multidimensional Scaling (NMDS). Optimal classification and the interpretation of multivariate analyses allowed us to recognize two major vegetation types and six clusters that were characterized by their floristic composition, altitudinal range and phytosociological classification. The first vegetation type (alliance Festucion burnatii, class Festuco Hystricis-Ononidetea) corresponds to stripped habitats subjected to cryoturbation and represented by two community types (Helianthemo cantabrici-Festucetum hystricis ass. nova and Jasiono cavanillesii-Helictotrichetum sedenensis ass. nova). A second vegetation type includes alpine-like communities with higher biomass (alliance Armerion cantabricae, class Festuco-Seslerietea) represented by snow-bed (Ranunculo carinthiaco-Poetum alpinae ass. nova), mesophilous (ass. Pediculari fallacis-Armerietum cantabricae) and scree (Saxifrago coniferae-Helianthemetum urrielensis ass. nova) grasslands; and relict wind-edge swards (alliance Oxytropido-Elynion, class Elynetalia myosuroidis) represented by relict alpine communities (ass. Oxytropido neglectae-Kobresietum myosuriodis). Our results highlight the Picos de Europa as a unique refuge for alpine vegetation and demonstrate historical relationships with both Alpine-Pyrenean and Iberian mountain ranges.